Current Account Imbalances in the Euro Area A Comparative Perspective - Barnes, Sebastian (OECD Publishing, 2010)
This paper considers the increase in current account imbalances in euro area countries since the early 1990s. While the euro area as a whole has remained relatively close to external balance, the current account balances of individual countries have diverged: Spain, Greece and Portugal ran large current account deficits by historical norms for industrial economies, while Germany and the Netherlands ran large surpluses. These imbalances are larger and more sustained than those observed in recent decades. While there has been extensive discussion of the US and Chinese external positions in the context of the debate on global imbalances, more attention has been given to the developments in the euro area only in the wake of the recent sovereign debt crisis. This paper uses a period-average model estimated on data for OECD countries since the late 1960s to investigate the determinants of current account imbalances. Fundamental economic factors are found to play an important role, in line with earlier studies, but do not fully explain the extent of imbalances over the past decade. The strength of housing investment appears to capture important effects over this period. This working paper relates to the 2010 OECD Economic Survey of the Euro Area (www.oecd.org/eco/surveys/euroarea)
Keywords: Economics; Euro Area